Development of Self Sensing Cementitious Composite Sensor Using Carbon Black for Performance Monitoring of Concrete - Dogra, Ashank (My University, 2024)
In recent years, an innovative method has been used to detect different structural conditions by incorporating steel and carbon fibers into a cementitious composite. This technique aims to reduce the resistivity of the composite and establish a piezoresistive matrix. Smart cement-based nanomaterials, such as graphene derivatives like carbon fiber or carbon nanotube cementitious hybrids, or a combination of both, function as sensors for structural health monitoring (SHM). These materials are piezo-resistive, meaning that their resistivity changes in response to applied stress or strain. This signifies that a cement sample or construction does not need the external or supplementary connection of any sensor. On the other hand, the cement composite has the capability to sense its own tension as well as several other elements. The current research describes the several tests conducted to assess the mechanical and electrical characteristics of cementitious mortar samples containing different proportions of CB (Carbon Black). Testing was conducted at intervals of 28, and 56 days throughout the curing process. The mechanical qualities were assessed by compressive strength and flexural strength tests, while the electrical properties were evaluated through electrical resistivity and piezo resistivity tests. The self-sensing capacity of the composite phase is due to the piezoresistive action of functional filler particles, which are uniformly distributed and establish a conductive link. Therefore, when a cementitious composite is subjected to external forces, the structure of the material changes, leading to a change in its electrical resistivity. The results from many experiments indicate that the addition of CB led to an improvement in both the compressive strength and flexural strength of the cementitious mortar after 28 days and 56 days. When CB is added at all addition percentages, the FCR (Fractional Change in Resistivity) lowers as the load increases. This drop correlates with an increase in electrical conductivity. After the sample fails under monotonic loading, the FCR returns to its previous value, which corresponds to a decrease in conductivity. Therefore, the piezoresistive behaviour consistently adheres to the overall pattern.
Keywords: Self-Sensing cementitious composite; Sensor; Carbon black; Monitoring